Choice Between Free Combination of Antihypertensive Agents and Fixed Dosed Combinations in the Treatment of Arterial Hypertension - O. S. Levchenkova; R. R. Galimulina; B. R. Komev; K. D. Zagnet (SINAPS LLC, 2024)
Most patients with arterial hypertension require more than one antihypertensive drug for blood pressure target achievement. Some patients are recommended for a multi-pill antihypertensive regimen, others - treatment with fixed dosed combinations in one tablet. Analysis of elibrary and PubMed publications in the period mostly from 2014 to 2024 concerning the choice of two-component combined antihypertensive agents containing renin-angiotensin system inhibitor and diuretic or calcium channel blocker, revealed that fixed-dose combinations (FDC) use and taking one tablet once a day improves adherence to treatment and facilitates blood pressure control. Although the cost of FDC containing the renin-angiotensin-aldosterone system inhibitor and a thiazide/thiazide-like diuretic or calcium channel blocker is in most cases higher than the same drugs taken separately, the use of fixed combinations, increasing patient adherence to therapy, has clinical advantage in terms of the effectiveness of lowering blood pressure, which confirms their economic feasibility. On the other hand, the use of free combination therapy in two different tablets, when taken separately during the day, can sometimes provide a more sustained antihypertensive effect over 24 hours. Evidence of the effectiveness of blood pressure control for FDCs is often extrapolated from data on free combinations. In addition, FDCs are characterized by less detection of possible ineffectiveness of one of the components. The range of FDCs and the dosage ratios of the components presented in them is gradually expanding, but the choice among free combinations is still wider. In addition, the list of vital and essential drugs (VED) for 2024 does not contain FDCs for antihypertensive drugs, which excludes the possibility of free receiving them on a preferential basis and gives the opportunity for the manufacturer to set prices for them. Despite the fact that recently the scientific community has recommended the use of FDC antihypertensive drugs as initial therapy due to better compliance with the regimen, and therefore clinical effectiveness and economic feasibility, it cannot be said that there is no space left for free combinations of antihypertensive drugs in the treatment of arterial hypertension. The choice of doctor, frequency of prescription, share of purchases of the FDCs in the Russian Federation, review of their consumption requires further analysis.